Radiographic Number of Positive Pelvic Lymph Nodes as a Prognostic Factor in Cervical Cancer Treated With Definitive Concurrent Chemoradiotherapy or Intensity-Modulated Radiotherapy - Wang, Shih-Chang; Lin, Li-Ching; Kuo, Yu-Ting; Lin, Yu-Wei (Frontiers in Oncology, 2018)
Background: This study aims to assess the prognostic significance of radiographic numbers of positive pelvic lymph nodes (PLNs) in patients with cervical cancer treated with definitive concurrent chemoradiotherapy (CCRT) or intensity-modulated radiotherapy (IMRT). Methods: We conducted a retrospective study that included 164 eligible adult patients with cervical cancer who were treated with definitive CCRT or IMRT at our institution from 2009 to 2016. After exclusion of 50 patients, a total of 114 patients whose clinicopathological data and follow-up were finally analyzed. The radiographic numbers of positive PLNs were assessed by pretreatment magnetic resonance imaging (MRI) or computed tomography (CT). The criterion for a positive lymph node was defined as a short-axis diameter >1 cm. Using the Kaplan–Meier method and the Cox proportional hazards regression model, we assessed the overall survival (OS), cancer-specific survival (CSS), distant metastasis-free survival (DMFS), and locoregional relapse-free survival (LRFS). Results: The median follow-up duration was 40 (range: 2–100) months. For patients with 0, 1–2, and ≥3 positive PLNs, the estimated 3-year OS were 85.4% vs. 82.4% vs. 59.7% (p = 0.035), CSS were 90.1% vs. 86.1% vs. 62.9% (p = 0.010), DMFS were 89.4% vs. 91.3% vs. 49.6% (p < 0.001), and LRFS were 77.8% vs. 73.4% vs. 70% (p = 0.690). Per the multivariate Cox regression, positive PLNs ≥3 (HR, 2.51; 95% CI: 1.09–5.80; p = 0.031) and non-squamous cell carcinoma type (HR, 2.82; 95% CI: 1.19–6.69; p = 0.018) were unfavorable factors for the OS. Besides, positive PLNs ≥3 was the independent factor for the CSS (HR, 3.38; 95% CI: 1.32–8.67; p = 0.011) and DMFS (HR, 6.83; 95% CI: 2.62–17.83; p < 0.001). The patients that were treated without intracavitary brachytherapy exhibited inferior LRFS (HR, 13.15; 95% CI: 2.66–65.10; p = 0.002). Conclusions: The radiographic number of positive PLNs (≥ 3) is an independent prognostic factor for OS, CSS, and DFMS in patients treated with definitive CCRT or IMRT.